Ethnopharmacological survey of aromatic and medicinal plants of the pharmacopoeia of northern Morocco - Labiad, Hanaa; Et-tahir, Aziz; Ghanmi, Mohamed; Satrani, Badr; Aljaiyash, Ahmed; Chaouch, Abdelaziz; Fadli, Mohamed (Ethnobotany Research and Applications, 2020)
Backgound: For centuries, Moroccan herbalists have been using traditional plant-based medicines; however, most of these traditional healers misuse their use because of the limited information about harmful side effects. The traditional healers prescribe recipes that do not comply with any quality standards. Materials and methods: This study was designed and initiated in an effort to classify and shortlist the most reported medicinal plants used by traditional healers in the northern part of Morocco and identify their associated toxicities. Data from this work was obtained by collecting semi-interviews and direct questionnaires from local traditional healers and guided fieldtrips with herbalists. Results: A total of 40 of the identified plant species belonged to 34 genera and 21 botanical families. The most represented were Lamiaceace (13 species) followed by Asteraceace (6 species) and Cupressaceae (3 species). The most frequently cited and used species were Mentha pulegium (22.5%) and Rosmarinus officinalis (15%). In addition, our survey revealed 11 recipes prepared from 40 species. Leaves were the most used parts with a percentage of 30.52% and the main preparation method was infusion (63%). It shows that these recipes are generally administered orally during seven, fifteen or even thirty days with an average of one to three cups a day. Some of these recipes are used to treat diseases of the digestive and nervous system. The local population, whose purchasing power is very low, uses the plants harvested directly in the study area causing the disappearance of the most vulnerable species. Conclusions: This study shows that traditional medicine is still used and constituted a very rich heritage in northern Morocco. Further investigation of the benefits and risks of these plants will be needed to guide ancestral knowledge during self-medication that causes negative effects on human health and will be needs planned exploitation. Keywords: Medicinal plants; Aromatic plants; Pharmacopoeia; Ethnopharmacology; Morocco